2017
DOI: 10.1093/mnras/stx1000
|View full text |Cite
|
Sign up to set email alerts
|

The SAMI Galaxy Survey: kinematics of dusty early-type galaxies

Abstract: Recently, large samples of visually classified early-type galaxies (ETGs) containing dust have been identified using space-based infrared observations with the Herschel Space Telescope. The presence of large quantities of dust in massive ETGs is peculiar as X-ray halos of these galaxies are expected to destroy dust in ∼10 7 yr (or less). This has sparked a debate regarding the origin of the dust: is it internally produced by asymptotic giant branch (AGB) stars, or is it accreted externally through mergers? We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 141 publications
(239 reference statements)
3
18
0
Order By: Relevance
“…We find that a similar fraction of our low-mass Es are also rotation dominated. Significant rotation has previously been observed in the stellar kinematics of early-type galaxies and, in particular, appears to be more common for low-mass early types (see e.g., Emsellem et al 2007;Brough et al 2017;van de Sande et al 2017a;Bassett et al 2017). It is also not surprising that Sd-Irr galaxies in this sample are typically found to be rotation dominated.…”
Section: Sami Kinematics Of Lbsssupporting
confidence: 54%
“…We find that a similar fraction of our low-mass Es are also rotation dominated. Significant rotation has previously been observed in the stellar kinematics of early-type galaxies and, in particular, appears to be more common for low-mass early types (see e.g., Emsellem et al 2007;Brough et al 2017;van de Sande et al 2017a;Bassett et al 2017). It is also not surprising that Sd-Irr galaxies in this sample are typically found to be rotation dominated.…”
Section: Sami Kinematics Of Lbsssupporting
confidence: 54%
“…However, its gas content would likely be substantially different from that of pSB galaxies. In particular, we should expect dry merger remnants to be even more gas-depleted than noninteracting QGs (see, e.g., Bassett et al 2017); while in its present state, our model would assign a higher f gas to them. This is illustrated by the different behavior at > 3 × 10 11 M of tracks with fixed and varying f g,0, f (Fig.…”
Section: Resultsmentioning
confidence: 74%
“…Xu, Narayanan, & Walker 2010), although recent integral field spectroscopy results have shown that ETGs do not necessarily require to accrete their dust content from merger events (e.g. Bassett et al 2017). These studies mostly concern large-scale structures, while the cases of inner rings similar to those presented in this paper remain still mysterious.…”
Section: Evolution Of Dust Rings and Llagns In Etgsmentioning
confidence: 71%